Open versus laparoscopic repair of perforated duodenal ulcer: a comparative study - Deshmukh, Santoshkumar N.; Parikh, Hirav P. (International Surgery Journal, 2020)
Background: Surgery is the mainstay of the treatment for perforated duodenal ulcer by closing the perforation with or without omental patch. There are no controversies in the surgical treatment of perforated duodenal ulcer but the best approach to surgery is still debatable. Advances in minimal access surgery has made it possible to close the perforated duodenal ulcer laparoscopically. The present study was conducted to compare the results of open and laparoscopic repair of perforated duodenal ulcer in terms of operative time, postoperative pain, hospital stay, and post-operative complications etc. Methods: The study was conducted in Dr. V. M. Government Medical College and Hospital located in Solapur (Maharashtra) from December 2008 to December 2010. It was a prospective comparative study. Patients were randomly divided into 2 groups alternately where group A and B were operated by conventional and laparoscopic techniques respectively and their outcomes were compared. Results: Most commonly affected age in this study was 51 to 60 years with male preponderance. Post-operative pain, analgesic requirement, wound infection, hospital stay, was significantly less in laparoscopic group as compared to open group (p<0.05). Conclusions: Laparoscopic repair of perforated duodenal ulcer is safe and feasible in properly selected patients and has superior results as compared to open surgery.